What's the Time? :The World of Eric Carle - Carle, Eric (PENGUIN BOOKS LIMITED (UK), 2016)
Learn to tell the time with the Very Hungry Caterpillar! When does the Very Hungry Caterpillar wake up? What time does the frog eat lunch? See what all your favourite animals do from breakfast to bedtime! And turn the chunky clock hands to show the time of day on every page. This book is a brilliant way to start learning how to tell the time. Featuring a sturdy clock with hands to turn, and adorable animals at different times of day, all accompanied by the beautiful artwork of Eric Carle.